Chiral geodesics in a stationary electromagnetic universe - Halilsoy, M.; Memari, V. (Elsevier, 2025)
The spinning electromagnetic universe, known also as the Rotating Bertotti-Robinson(RBR) spacetime is considered in which attractive electromagnetic energy races with centrifugal force. The model derives from different physical considerations, such as colliding waves, throat region, and near horizon geometry of the Kerr-Newman black hole. Stated otherwise, although our spacetime is not a black hole (BH) spacetime it is connected to a BH indirectly. Our interest is whether such a singularity-free spinning cosmology consisting of electromagnetic fields alone gives rise to a natural direction of flow, a 'chirality' for charged particles. The vast majority of our cosmos consists of vacuum filled by the cosmic microwave background (CMB) and our RBR maybe considered as a representative model for such electrovacua. It is observed that the magnetic field in evolutionary cosmology is crucial. We also show the occurrence of closed timelike curves a 'la' G & ouml;del. Such curves, however, seem possible only at localized cell structures, not at large scales, but according to our prescription of near horizon geometry, they arise in the vicinity i.e. near horizon of a charged, spinning black hole.